2006
DOI: 10.1074/jbc.m513481200
|View full text |Cite
|
Sign up to set email alerts
|

ω-Oxidation of Very Long-chain Fatty Acids in Human Liver Microsomes

Abstract: X-linked adrenoleukodystrophy (X-ALD) is a severe neurodegenerative disorder biochemically characterized by elevated levels of very long-chain fatty acids (VLCFA). Excess levels of VLCFAs are thought to play an important role in the pathogenesis of X-ALD. Therefore, therapeutic approaches for X-ALD are focused on the reduction or normalization of VLCFAs. In this study, we investigated an alternative oxidation route for VLCFAs, namely -oxidation. The results described in this study show that VLCFAs are substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
45
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 41 publications
1
45
0
Order By: Relevance
“…C22:0, C24:0, and C26:0). This suggested that the induction of these enzymes could represent a potential therapeutic target for treatment of X-linked adenoleukodystrophy (X-ALD) disease (15). X-ALD is a recessive genetic disease and is characterized by a defect in peroxisomal ␤-oxidation of very long chain fatty acids with secondary neuroinflammatory damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…C22:0, C24:0, and C26:0). This suggested that the induction of these enzymes could represent a potential therapeutic target for treatment of X-linked adenoleukodystrophy (X-ALD) disease (15). X-ALD is a recessive genetic disease and is characterized by a defect in peroxisomal ␤-oxidation of very long chain fatty acids with secondary neuroinflammatory damage.…”
Section: Discussionmentioning
confidence: 99%
“…Antibody inhibition experiments (13,14) suggest that P450 4F2/4F3B in human liver and kidney microsomes contribute ϳ66% to the formation of 20-HETE. Recently, P450s 4F2 and 4F3B were found to -hydroxylate very long chain saturated fatty acids (15) as well as phytanic acid (16). Our preliminary experiments using com-mercially available Supersomes TM (BD Gentest) indicate that P450 4F2 also -hydroxylates oleic acid, stearic acid, and palmitic acid, but not lauric acid.…”
mentioning
confidence: 99%
“…The experimental conditions to study the -oxidation of -hydroxy fatty acids were the same as those described previously (17,20) with minor modifications, as discussed below.…”
Section: Enzymatic -Oxidation Assaysmentioning
confidence: 99%
“…Recently, we demonstrated that VLCFAs can also be oxidized via another mechanism, i.e., -oxidation (17). The first step in this pathway involves the hydroxylation of the -methyl group of the VLCFA, generating a -hydroxy-VLCFA.…”
mentioning
confidence: 99%
See 1 more Smart Citation